Multilayer structure, vacuum packaging bag and vacuum insulation
By using a biaxially stretched polyvinyl alcohol-based resin film as a base material in the multilayer structure of the vacuum insulator and adding modified polyvinyl alcohol to the outer coating, the problem of reducing barrier properties of the vacuum insulator under physical stress is solved, and a combination of high bending resistance and high barrier properties is achieved.
Patent Information
- Application Number
- CN202080059584.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-23
- Filing Date
- 2020-08-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-08-21
AI Technical Summary
When existing vacuum insulators withstand physical stresses, their barrier properties are easily reduced, especially under stresses such as bending.
The design of a multilayer structure is adopted, wherein the substrate is formed of a biaxially stretched polyvinyl alcohol resin film, the outer coating includes modified polyvinyl alcohol, the modified polyvinyl alcohol has vinyl alcohol units and monomer units with polar groups, and the thickness of the outer coating is 0.003 μm or more and 5 μm or less.
When withstanding physical stresses such as bending, the multilayer structure can maintain high barrier properties, significantly improving the bending resistance of vacuum packaging bags and vacuum insulators.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a multilayer structure, a vacuum packaging bag and a vacuum thermal insulation body. Background Art
[0002] In the past, polyurethane foam was widely used as an insulator used in refrigerators, residential insulation walls, storage tanks, etc. In recent years, vacuum insulators have been used as an insulator to replace it. Vacuum insulators can achieve the same insulation properties as those of insulators formed by urethane foam in a thinner and lighter form. Vacuum insulators are used as insulators for insulating heat transfer machines such as heat pump application machines, heat storage machines, living spaces, vehicle interiors, etc., and their uses and demand are gradually expanding.
[0003] As a vacuum insulator, for example, there is a structure including a vacuum packaging bag and a core material, wherein the core material is arranged inside the vacuum packaging bag. One of the properties required of the vacuum packaging bag is barrier property. Therefore, a vacuum packaging bag with improved barrier property and a barrier film used therein are proposed.
[0004] For example, Patent Document 1 describes a gas barrier film as a film used for a vacuum packaging bag having improved gas barrier properties, wherein the film has a vapor-deposited film on one side of an ethylene-vinyl alcohol copolymer film and has a coating layer adjacent to the vapor-deposited film, wherein the polyvinyl alcohol in the coating layer contains an inorganic substance.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-114520. Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, the above-mentioned conventional gas barrier films may have reduced barrier properties when subjected to physical stress such as stretching or bending during the manufacturing process of vacuum insulators or the like.
[0010] An object of the present invention is to provide a multilayer structure, a vacuum packaging bag, and a vacuum thermal insulator that can maintain high barrier properties even when subjected to physical stress such as bending.
[0011] Solutions for solving problems
[0012] That is, the present invention is achieved by providing the following solutions:
[0013] [1] A multilayer structure comprising, in order, a substrate (X), an inorganic deposited layer (Y), and an outer coating layer (Z), wherein the substrate (X) is formed of a biaxially stretched polyvinyl alcohol-based resin film, the outer coating layer (Z) comprises a modified polyvinyl alcohol (A), the modified polyvinyl alcohol (A) having a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the vinyl alcohol unit (a), and the thickness of the outer coating layer (Z) is 0.003 μm or more and 5 μm or less;
[0014] [2] The multilayer structure according to [1], wherein the ratio of the monomer unit (b) having a polar group in all monomer units constituting the modified polyvinyl alcohol (A) is 0.05 mol% or more and 30 mol% or less;
[0015] [3] The multilayer structure according to [1] or [2], wherein the polar group is at least one selected from a carboxyl group, an ester group and a silanol group;
[0016] [4] The multilayer structure according to any one of [1] to [3], wherein the maximum intensity ratio (I(B) / I(C)) obtained by the following steps (1) to (3) is MAX ) is 1.20 or more,
[0017] (1) Five randomly selected locations on the surface of the outer coating layer (Z) were analyzed in the depth direction using TOF-SIMS.
[0018] (2) For each detected fragment, the average value of the maximum intensity of the fragment at each measurement site (I(B)) and the average value of the intensity at the measurement point between the measurement start point and the maximum intensity measurement point of each measurement site (I(C)) are calculated, and their ratio is taken as the intensity ratio (I(B) / I(C)).
[0019] (3) The maximum intensity ratio among the intensity ratios (I(B) / I(C)) of each fragment is taken as the maximum intensity ratio (I(B) / I(C)). MAX ).
[0020] [5] The multilayer structure according to any one of [1] to [4], further comprising another layer (J) in addition to the substrate (X), the inorganic deposited layer (Y) and the topcoat layer (Z);
[0021] [6] The multilayer structure according to [5], comprising at least two of the other layers (J), and a substrate (X), an inorganic vapor-deposited layer (Y) and an outer coating layer (Z) between the at least two other layers (J);
[0022] [7] The multilayer structure according to any one of [1] to [6], wherein the biaxially stretched polyvinyl alcohol-based resin film is a biaxially stretched film having as a main component an ethylene-vinyl alcohol copolymer having an ethylene unit content of 10 mol % to 65 mol % and a saponification degree of 90 mol % or more;
[0023] [8] The multilayer structure according to any one of [1] to [7], wherein the oxygen permeability measured according to JIS K7126 at 40°C, 0% RH (carrier gas side) and 90% RH (oxygen supply side) after three reciprocating movements in a Gelbo Flex test according to ASTM F392 is 2.0 ml / (m 2 ・day・atm) or less;
[0024] [9] A vacuum packaging bag comprising the multilayer structure according to any one of [1] to [8];
[0025]
[10] A vacuum thermal insulator comprising the vacuum packaging bag of [9] and a core material arranged inside the vacuum packaging bag, wherein the inside of the vacuum packaging bag is decompressed.
[0026] Effects of the Invention
[0027] According to the present invention, a multilayer structure, a vacuum packaging bag, and a vacuum thermal insulator that can maintain high barrier properties even when subjected to physical stress such as bending can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a diagram showing one of the measurement results of SiO 2 in the depth direction analysis obtained using TOF-SIMS in Example 4. DETAILED DESCRIPTION
[0029] In this specification, "gas barrier properties" refers to the performance of blocking gases other than water vapor unless otherwise specified. In addition, when abbreviated as "barrier properties" in this specification, it refers to both gas barrier properties and water vapor barrier properties. In addition, the property of "maintaining high barrier properties even when subjected to physical stress such as bending" is sometimes expressed as "bending resistance".
[0030] (Multilayer structure)
[0031] The multilayer structure of the present invention comprises a substrate (X), an inorganic vapor-deposited layer (Y) and an outer coating layer (Z) in sequence, wherein the substrate (X) is formed by a biaxially stretched polyvinyl alcohol-based resin film (hereinafter sometimes abbreviated as a "biaxially stretched PVA-based resin film"), and the outer coating layer (Z) comprises a modified polyvinyl alcohol (A) (hereinafter sometimes abbreviated as a "modified PVA (A)"), wherein the modified polyvinyl alcohol (A) comprises a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the aforementioned vinyl alcohol unit (a), and the thickness of the outer coating layer (Z) is greater than 0.003 μm and less than 5 μm. The multilayer structure of the present invention has a tendency to exhibit good bending resistance by having an inorganic vapor-deposited layer (Y) on the substrate (X) and having an outer coating layer (Z) comprising the modified PVA (A) at a specific thickness. It should be noted that in the multilayer structure, the substrate (X) and the inorganic vapor-deposited layer (Y) may be in direct contact with each other, or may be sandwiched between other layers. Similarly, the inorganic vapor-deposited layer (Y) and the outer coating layer (Z) may be in direct contact or may be interposed with other layers, and the inorganic vapor-deposited layer (Y) and the outer coating layer (Z) are preferably in direct contact. In addition, in the multilayer structure, the inorganic vapor-deposited layer (Y) and the outer coating layer (Z) may be provided on both sides of the substrate (X), respectively.
[0032] (Base material (X))
[0033] The multilayer structure of the present invention exhibits excellent gas barrier properties by having a substrate (X) formed of a biaxially stretched PVA-based resin film. In addition, since the substrate (X) is composed of a biaxially stretched PVA-based resin film, the affinity with the inorganic vapor-deposited layer (Y) described later is improved, and the bending resistance is improved.
[0034] The biaxially stretched PVA resin film is a biaxially stretched film having a PVA resin as the main component. The main component refers to the component with the largest content based on mass. The content of the PVA resin in the substrate (X), i.e., the biaxially stretched PVA resin film, is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 99% by mass or more.
[0035] As the PVA-based resin, any resin having a vinyl alcohol unit obtained by saponifying a vinyl ester unit may be used, and examples thereof include polyvinyl alcohol (hereinafter sometimes abbreviated as "PVA") resin and ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as "EVOH") resin. Among them, from the viewpoint of obtaining a multilayer structure having better bending resistance, the PVA-based resin is preferably an EVOH resin. That is, the substrate (X) is preferably formed of a biaxially stretched EVOH resin film.
[0036] As PVA resin, for example, PVA resins obtained by polymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate and vinyl versatate separately, followed by saponification, can be cited. In addition, the PVA resin in the present invention can be a modified PVA resin obtained by copolymerization modification or post-modification. The homopolymerization of vinyl ester and the saponification of vinyl ester homopolymers can be carried out by known methods. In addition, the copolymerized modified PVA resin is manufactured by, for example, copolymerizing the aforementioned vinyl ester with an unsaturated monomer copolymerizable with the vinyl ester, followed by saponification, and the amount of modification is usually less than 10 mol%.
[0037] Examples of the unsaturated monomers copolymerizable with the vinyl ester include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 4-pentene-1-ol, and 5-hexene-1-ol, and their acylated derivatives; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid, and their salts, monoesters, or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; diacetone acrylamide, acrylamide, and methacrylamide. Amides; olefin sulfonic acids or their salts such as ethylene sulfonic acid, allyl sulfonic acid, and methyl allyl sulfonic acid; vinyl compounds such as alkyl vinyl ether, dimethyl allyl vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxolane, glycerol monoallyl ether, 3,4-diacetoxy-1-butene; substituted vinyl acetates such as isopropenyl acetate and 1-methoxyvinyl acetate; vinylidene chloride, 1,4-diacetoxy-2-butene, vinyl carbonate, etc.
[0038] The post-modified PVA resin is obtained by post-modifying PVA by methods such as acetoacetation, acetalization, urethanization, etherification, grafting, phosphate esterification, and oxyalkylene esterification.
[0039] In the present invention, the viscosity average polymerization degree of the PVA resin is preferably 1100 or more, more preferably 1200 or more. In addition, the viscosity average polymerization degree of the PVA resin is preferably 4000 or less, more preferably 2600 or less. If the viscosity average polymerization degree of the PVA resin is 1100 or more, the mechanical strength of the obtained vacuum packaging bag becomes good, so it is preferred. On the other hand, if the viscosity average polymerization degree is 4000 or less, the processability during film formation and stretching becomes good, so it is preferred. In addition, the saponification degree of the PVA resin is preferably 90 mol% or more, more preferably 95 mol% or more, and further preferably 99 mol% or more. In addition, the saponification degree of the PVA resin can be 100 mol% or less, or 99.9 mol% or less. If the saponification degree is within the above range, the water resistance is improved, and the gas barrier property against humidity becomes good, so it is preferred. The viscosity average polymerization degree and saponification degree of the PVA resin can be measured according to the method described in JIS K 6726 (1994).
[0040] EVOH resin is usually obtained by saponifying a copolymer of ethylene and a vinyl ester such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate and vinyl versatate. The production and saponification of the copolymer of ethylene and vinyl ester can be carried out by a known method. The saponification degree of the vinyl ester component of the EVOH resin is preferably 90 mol% or more, more preferably 95 mol% or more, and further preferably 99 mol% or more. By setting the saponification degree to 90 mol% or more, the gas barrier properties can be improved. The saponification degree of EVOH resin can be 100 mol% or less, or 99.99 mol% or less. The saponification degree of EVOH resin is determined by performing nuclear magnetic resonance (NMR). 1 H-NMR) measurement, and the peak area of hydrogen atoms contained in the vinyl ester structure and the peak area of hydrogen atoms contained in the vinyl alcohol structure were measured to determine.
[0041] The ethylene unit content of EVOH resin is preferably 10 mol% or more, more preferably 15 mol% or more, further preferably 20 mol% or more, and further preferably 25 mol% or more. In addition, the ethylene unit content of EVOH resin is preferably 65 mol% or less, more preferably 55 mol% or less, and further preferably 50 mol% or less. If the ethylene unit content is 10 mol% or more, it shows a tendency to be able to well maintain gas barrier properties and bending resistance under high humidity. On the other hand, if the ethylene unit content is 65 mol% or less, the gas barrier properties can be improved. The ethylene unit content of EVOH resin can be obtained by NMR method.
[0042] In addition, the EVOH resin may have units derived from other monomers other than ethylene, vinyl esters and saponified products thereof within the scope that does not impair the purpose of the present invention. When the EVOH resin has the aforementioned other monomer units, the content of the aforementioned other monomer units relative to the total monomer units of the EVOH resin is 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, and particularly preferably 5 mol% or less. In addition, when the EVOH resin has units derived from the aforementioned other monomers, the lower limit value may be 0.05 mol% or 0.10 mol%. Examples of the other monomers include olefins such as propylene, butene, pentene, and hexene; 3-acyloxy-1-propylene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, 5,6-diacyloxy-1-hexene; , 1,3-diacetoxy-2-methylenepropane and other olefins having an ester group or their saponification products; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid or their anhydrides, salts, or monoalkyl esters or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, methyl allyl sulfonic acid or their salts; vinyl silane compounds such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxy-ethoxy) silane, γ-methacryloxypropyl methoxysilane; alkyl vinyl ethers, vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinylidene chloride, etc.
[0043] When the EVOH resin is a blend of two or more different EVOH resins, the average ethylene unit content or saponification degree of the entire EVOH resin is taken as the ethylene unit content or saponification degree of the EVOH resin.
[0044] The biaxially stretched PVA resin film may contain other ingredients such as carboxylic acid compounds, phosphoric acid compounds, boron compounds, metal salts, stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, various fibers and other reinforcing agents as long as the effects of the present invention are not impaired.
[0045] As the substrate (X), a film made of a PVA-based resin is used. The film-making method of the film can be a known method, for example, a casting method in which a solution of a PVA-based resin is cast on a metal surface such as a drum or an endless belt to form a film; or a melt forming method in which melt extrusion is performed by an extruder.
[0046] The PVA resin film is biaxially stretched according to known methods such as simultaneous biaxial stretching and sequential biaxial stretching for use. As the stretching ratio, from the viewpoints of thickness uniformity, barrier properties, mechanical properties and film-forming properties, it is preferred that the longitudinal direction (MD direction) is 2.5 times or more and 4.5 times or less, the transverse direction (TD direction) is 2.5 times or more and 4.5 times or less, and the surface stretching ratio is 7 times or more and 15 times or less, and it is more preferred that the longitudinal direction is 2.5 times or more and 3.5 times or less, the transverse direction is 2.5 times or more and 3.5 times or less, and the surface stretching ratio is 8 times or more and 12 times or less. If the PVA resin film is not biaxially stretched, the bending resistance and gas barrier properties may sometimes be reduced.
[0047] The thickness of the substrate (X) is not particularly limited, but is preferably 5 μm or more, more preferably 8 μm or more, and further preferably 10 μm or more from the viewpoint of industrial productivity. In addition, the thickness of the substrate (X) is preferably 100 μm or less, more preferably 50 μm or less, further preferably 40 μm or less, and particularly preferably 30 μm or less. It should be noted that the thickness refers to the average value of the values measured at any five points. The same applies to other thicknesses below.
[0048] (Inorganic vapor deposition layer (Y))
[0049] The inorganic vapor-deposited layer (Y) is a layer that generally has barrier properties to oxygen and water vapor, and can be formed by vapor-depositing an inorganic substance. Examples of the inorganic substance include metals (e.g., aluminum), metal oxides (e.g., silicon oxide, aluminum oxide), metal nitrides (e.g., silicon nitride), metal oxynitrides (e.g., silicon oxynitride), and metal carbonitrides (e.g., silicon carbonitride). Among them, aluminum, aluminum oxide, silicon oxide, magnesium oxide, or silicon nitride is preferred from the viewpoint of excellent barrier properties after bending, and aluminum is more preferred.
[0050] The method for forming the inorganic vapor deposition layer (Y) is not particularly limited, and examples thereof include physical vapor growth methods such as vacuum vapor deposition (e.g., resistance heating vapor deposition, electron beam vapor deposition, molecular beam epitaxy, etc.), sputtering, and ion plating; chemical vapor growth methods such as thermal chemical vapor growth (e.g., catalytic chemical vapor growth), photochemical vapor growth, plasma chemical vapor growth (e.g., capacitively coupled plasma, inductively coupled plasma, surface wave plasma, electron cyclotron resonance, dual magnetron, atomic layer deposition, etc.), and organic metal vapor growth.
[0051] The thickness of the inorganic vapor-deposited layer (Y) varies depending on the type of components constituting the inorganic vapor-deposited layer (Y), and is preferably 0.002 μm or more and 0.5 μm or less, more preferably 0.005 μm or more and 0.2 μm or less, and further preferably 0.01 μm or more and 0.1 μm or less. If the thickness of the inorganic vapor-deposited layer (Y) is 0.002 μm or more, the barrier properties to oxygen and water vapor tend to become better. In addition, if the thickness of the inorganic vapor-deposited layer (Y) is 0.5 μm or less, the barrier properties after bending tend to be further maintained.
[0052] (Outer coating (Z))
[0053] The outer coating layer (Z) contains a modified PVA (A). By making the outer coating layer (Z) contain a modified PVA (A), the bending resistance tends to be improved. The modified PVA (A) has a vinyl alcohol unit (a) and a monomer unit (b) having a polar group. The monomer unit (b) does not include a vinyl alcohol unit (a). The modified PVA (A) is not particularly limited as long as it has a vinyl alcohol unit (a) and a monomer unit (b), and is preferably not modified with an alkylene group.
[0054] The vinyl alcohol unit (a) is a unit represented by -CH2CH(OH)-. The proportion of the vinyl alcohol unit (a) in all monomer units constituting the modified PVA (A) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 75 mol% or more, and further preferably 80 mol%, 85 mol%, 90 mol% or 95 mol% or more.
[0055] The monomer unit (b) is a monomer unit other than the vinyl alcohol unit (a), and has a polar group. The polar group may be a monovalent group or a divalent or higher group. The polar group is not particularly limited, but from the viewpoint of further improving the bending resistance, it is preferably at least one selected from a carboxyl group, an ester group (-COO-) and a silanol group. Among the polar groups, as a group containing an ester group, a group represented by -COOR (R is a hydrocarbon group) may be used. As the hydrocarbon group represented by the above R, an alkyl group is preferably used, and an alkyl group having 1 to 3 carbon atoms is more preferably used. The silanol group refers to a group (Si-OH) having a hydroxyl group (-OH) bonded to a silicon atom.
[0056] The modified PVA (A) can be produced by copolymerization modification, post-modification or other methods, similarly to the modified PVA that can be used for the above-mentioned substrate (X).
[0057] For example, the monomer unit (b) having a carboxyl group can be introduced into the modified PVA (A) by using an unsaturated acid such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, undecylenic acid, etc. as an unsaturated monomer. The monomer unit (b) having an ester group can be introduced into the modified PVA (A) by using an ester of an unsaturated acid, etc. as an unsaturated monomer, adjusting the saponification degree, etc. The monomer unit (c) having a silanol group can be introduced into the modified PVA (A) by using a compound having an unsaturated double bond and a trialkoxysilyl group such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxy-ethoxy)silane, γ-methacryloxypropylmethoxysilane, etc. as an unsaturated monomer. At least a portion of the trialkoxysilyl group forms a silanol group as the saponification proceeds.
[0058] The proportion of the monomer unit (b) having a polar group in all monomer units constituting the modified PVA (A) is preferably 0.05 mol% or more, more preferably 0.10 mol% or more. In addition, the proportion of the monomer unit (b) having a polar group is preferably 30 mol% or less, more preferably 25 mol% or less.
[0059] When the modified PVA (A) has a monomer unit (b) containing a carboxyl group as a polar group, the proportion of the monomer unit (b) containing a carboxyl group in all the monomer units constituting the modified PVA (A) is preferably 0.05 mol% or more, more preferably 0.50 mol% or more. In addition, the proportion of the monomer unit (b) containing a carboxyl group is preferably 10 mol% or less, more preferably 5 mol% or less. If the proportion of the monomer unit (b) containing a carboxyl group is within the above range, there is a tendency to show better bending resistance.
[0060] When the modified PVA (A) has a monomer unit (b) containing an ester group as a polar group, the proportion of the monomer unit (b) containing an ester group in all the monomer units constituting the modified PVA (A) is preferably 5 mol% or more, more preferably 10 mol% or more. In addition, the proportion of the monomer unit (b) containing an ester group is preferably 30 mol% or less, more preferably 25 mol% or less. If the proportion of the monomer unit (b) containing an ester group is within the above range, there is a tendency to show better bending resistance.
[0061] When the modified PVA (A) has a monomer unit (b) containing a silanol group as a polar group, the proportion of the monomer unit (b) containing a silanol group in all the monomer units constituting the modified PVA (A) is preferably 0.05 mol% or more, more preferably 0.1 mol% or more. In addition, the proportion of the monomer unit (b) containing a silanol group is preferably 5 mol% or less, more preferably 2 mol% or less. If the proportion of the monomer unit (b) containing a silanol group is within the above range, there is a tendency to show better bending resistance.
[0062] The modified PVA (A) may have a monomer unit (b) containing a carboxyl group or a silanol group, and may further have a monomer unit (b) containing an ester group. At this time, the suitable ratio of the monomer unit (b) containing a carboxyl group or a silanol group in all the monomer units constituting the modified PVA (A) is the same as the suitable ratio of the monomer unit (b) containing a carboxyl group or a silanol group mentioned above. On the other hand, the ratio of the monomer unit (b) containing an ester group in all the monomer units constituting the modified PVA (A) at this time is sometimes preferably 0.1 mol% or more and 10 mol% or less, more preferably 0.3 mol% or more and 5 mol% or less, and further preferably 1 mol% or more and 3 mol% or less. If the ratio of each monomer unit is within the above range, there is a tendency to have better bending resistance.
[0063] The total content of the vinyl alcohol unit (a) and the monomer unit (b) having a polar group in all monomer units constituting the modified PVA (A) is preferably 95 mol % or more, more preferably 99 mol % or more, and even more preferably 99.9 mol % or more.
[0064] The viscosity average degree of polymerization of the modified PVA (A) is preferably 1000 or more and 4000 or less, and more preferably 1200 or more and 2600 or less. If the viscosity average degree of polymerization of the modified PVA (A) is 1000 or more, the mechanical strength of the obtained vacuum packaging bag becomes good, which is preferred. On the other hand, if the viscosity average degree of polymerization is 4000 or less, the film forming properties and the like become good, which is preferred.
[0065] From the viewpoint of improving bending resistance, the content of modified PVA (A) in the outer coating layer (Z) is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and may be 95% by mass or more. The outer coating layer (Z) may consist essentially only of modified PVA (A), or may consist only of modified PVA (A).
[0066] The outer coating layer (Z) may contain other components in addition to the modified PVA (A) within a range that does not impair the effects of the present invention. Other components that may be contained in the outer coating layer (Z) include inorganic acid metal salts such as carbonates, hydrochlorides, nitrates, bicarbonates, sulfates, bisulfates, and borates; organic acid metal salts such as oxalates, acetates, tartrates, and stearates; metal complexes such as cyclopentadienyl metal complexes (such as titanocene) and cyanometallic complexes (such as Prussian blue); layered clay compounds, crosslinking agents, polymer compounds other than modified PVA (A), plasticizers, antioxidants, ultraviolet absorbers, flame retardants, etc. The content of the above-mentioned other components in the outer coating layer (Z) is preferably less than 50% by mass, more preferably less than 20% by mass, further preferably less than 10% by mass, particularly preferably less than 5% by mass, and may be 0% by mass (excluding other components).
[0067] The thickness of the outer coating layer (Z) is 0.003 μm or more, preferably 0.02 μm or more, and more preferably 0.06 μm or more. In addition, the thickness of the outer coating layer (Z) is 5 μm or less, preferably 1 μm or less, more preferably 0.5 μm or less, further preferably 0.2 μm or less, and particularly preferably 0.15 μm or less. If the thickness of the outer coating layer (Z) is outside the above range, the barrier properties after bending tend to decrease.
[0068] For the outer coating (Z), the maximum intensity ratio (I(B) / I(C)) obtained by the following steps (1) to (3) MAX ) is preferably greater than 1.20.
[0069] (1) Five randomly selected locations on the surface of the overcoat layer (Z) were analyzed in the depth direction (inorganic vapor deposited layer (Y) direction) using TOF-SIMS (time-of-flight secondary ion mass spectrometry).
[0070] (2) For each detected fragment, the average value of the maximum intensity of the fragment at each measurement location (I(B)) and the average value of the intensity at the midpoint between the measurement start point (surface) and the maximum intensity measurement point at each measurement location (I(C)) are calculated, and their ratio is taken as the intensity ratio (I(B) / I(C)).
[0071] (3) The maximum intensity ratio among the intensity ratios (I(B) / I(C)) of each fragment is taken as the maximum intensity ratio (I(B) / I(C)). MAX ).
[0072] TOF-SIMS is an analysis method that irradiates the sample with an ion beam (primary ion), obtains the released secondary ions (fragments) in a TOF (Time Of Flight) manner, and performs mass spectrometry analysis. It can use sputtered ions in the analysis in the depth direction, and perform the analysis in the depth direction while sputtering the multilayer structure. Therefore, in the analysis in the depth direction using TOF-SIMS, the measurement points can be obtained intermittently. "Arbitrary selection of 5 locations" refers to 5 locations randomly selected on the surface of the outer coating (Z) of the multilayer structure, and the range of analysis at each measurement location is 250μm×250μm. Since the maximum intensity is measured at the measurement locations of the arbitrarily selected 5 locations, the average value is recorded as I (B), and the average value of the measurement start point and the middle measurement point of the maximum intensity measurement point measured at each measurement location is recorded as I (C). For example, when the maximum intensity is obtained at the 11th measurement point, the 6th point becomes the middle measurement point, and when the maximum intensity is obtained at the 10th measurement point, the 5th and 6th measurement points become the middle measurement points. In addition, I(B) and I(C) are calculated for each fragment, and the intensity ratio (I(B) / I(C)) is also calculated for each fragment. The maximum intensity ratio among the intensity ratios (I(B) / I(C)) of each fragment is recorded as the maximum intensity ratio (I(B) / I(C)). MAX ).
[0073] Maximum intensity ratio (I(B) / I(C) MAX ) can be used as an indicator of the degree of partial existence of fragments. If the maximum intensity ratio (I(B) / I(C) MAX ) is close to 1, it can be judged as a uniform distribution. If (I(B) / I(C) MAX ) is large, it can be judged that there is a tendency of partial presence. In the present invention, as an indicator to ensure that the polar groups are partial at the interface between the outer coating layer (Z) and the inorganic vapor deposition layer (Y), the maximum intensity ratio (I (B) / I (C) MAX ), (I(B) / I(C) MAX ) is 1.20 or more, it is considered that the vicinity of the measurement point showing the maximum intensity I(B) is the interface between the overcoat layer (Z) and the inorganic vapor-deposited layer (Y).
[0074] Maximum intensity ratio of outer coating (Z) (I(B) / I(C) MAX ) is preferably 1.20 or more, more preferably 1.40 or more, further preferably 1.70 or more, and particularly preferably 2.00 or more. If the maximum intensity ratio (I(B) / I(C)) of the outer coating layer (Z) is MAX) is greater than the above lower limit, the polar groups in the outer coating layer (Z) tend to be concentrated at the interface between the outer coating layer (Z) and the inorganic vapor-deposited layer (Y), and as a result, the bending resistance tends to be improved. On the other hand, the maximum strength ratio (I(B) / I(C) MAX ) can be 5.00 or less, 4.00 or less, or 3.00 or less.
[0075] The fragments of the outer coating layer (Z) observed by TOF-SIMS are not particularly limited, and examples thereof include silicon-based fragments such as SiO2, alcohol-based fragments such as C2H3O and C3H5O, etc. Specifically, the surface analysis of the outer coating layer (Z) in the depth direction obtained by TOF-SIMS can be measured by the method described in the Examples.
[0076] (Method for producing multilayer structure)
[0077] The method for producing the multilayer structure of the present invention is not particularly limited, and examples thereof include a method comprising the following steps: step (i), applying a coating liquid (S) comprising a modified PVA (A) and a solvent onto an inorganic vapor-deposited layer (Y) of a laminate having an inorganic vapor-deposited layer (Y) on one side of a substrate (X); and step (ii), removing the solvent from the applied coating liquid (S) to form an outer coating layer (Z).
[0078] The laminate having the inorganic vapor-deposited layer (Y) on one side of the substrate (X) used in step (i) can be prepared by the same method as the method for forming the inorganic vapor-deposited layer (Y) described above. A commercially available laminate having the inorganic vapor-deposited layer (Y) on one side of the substrate (X) can also be used.
[0079] In the step (ii), a coating liquid (S) containing the modified PVA (A) and a solvent is applied onto the inorganic deposited layer (Y).
[0080] The solvent used in the coating liquid (S) is not particularly limited, but preferably contains water as the main component, and may contain only water. When containing water as the main component, other solvents used are preferably alcohols such as methanol, ethanol, and isopropanol.
[0081] The solid content concentration of the coating liquid (S) is preferably 0.01 to 15% by mass, more preferably 0.05 to 10% by mass, and even more preferably 0.1 to 5% by mass, from the viewpoints of the storage stability of the coating liquid (S), the coating properties for the inorganic vapor-deposited layer (Y), the degree of predominance of polar groups in the obtained overcoat layer (Z), etc. The solid content concentration can be calculated by, for example, dividing the mass of the solid content remaining after distilling off the solvent of the coating liquid (S) by the mass of the coating liquid (S) to be treated.
[0082] The coating method of the coating liquid (S) is not particularly limited, and known methods such as casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kiss coating, die coating, metering rod coating, sealed blade coating, curtain coating, and rod coating can be used.
[0083] The thickness of the layer (Z) formed by applying the coating liquid (S) to the inorganic deposited layer (Y) can be controlled by the solid content concentration of the coating liquid (S) or the coating method. For example, in the case of the gravure coating method, the groove volume of the gravure roll can be changed.
[0084] In step (ii), the solvent in the coating liquid (S) applied on the inorganic vapor-deposited layer (Y) is removed, thereby forming an outer coating layer (Z) on the inorganic vapor-deposited layer (Y). The method for removing the solvent from the applied coating liquid (S) is not particularly limited, and for example, a known drying method can be applied. Examples of drying methods include hot air drying, hot roller contact, infrared heating, and microwave heating. The drying temperature can be, for example, 80°C or higher and 180°C or lower, or 90°C or higher and 150°C or lower.
[0085] It should be noted that it is preferred that the coating liquid (S) is applied to the inorganic vapor-deposited layer (Y) and then dried after being allowed to stand. The standing time from coating to drying is, for example, more than 1 second, preferably more than 2 seconds. In addition, the standing time may be, for example, less than 1 minute. By allowing it to stand in advance in this way, there is a tendency to promote the polar groups in the formed outer coating (Z) to be biased toward the interface with the inorganic vapor-deposited layer (Y). In addition, in order to promote the aforementioned biased existence, it is also preferred that the solid content concentration of the coating liquid (S) is set to a lower range. In this way, by keeping the flow state of the coating liquid (S) on the inorganic vapor-deposited layer (Y) longer, there is a tendency to promote the aforementioned biased existence.
[0086] (Other layers (J))
[0087] In the multilayer structure of the present invention, in order to improve various properties (such as heat sealability, barrier properties, mechanical properties, etc.), other layers (J) other than the substrate (X), the inorganic vapor-deposited layer (Y) and the outer coating (Z) may be included. Such a multilayer structure of the present invention can be manufactured by, for example, further bonding or forming other layers (J) on a laminate having a substrate (X), an inorganic vapor-deposited layer (Y) and an outer coating (Z) directly or with the aid of an adhesive layer. As other layers (J), thermoplastic resin layers such as ink layers, polyolefin layers, polyester layers, polyamide layers, and ethylene-vinyl alcohol copolymer resin layers can be listed, but are not limited to them. The adhesive layer is also an example of other layers (J). The multilayer structure of the present invention preferably has at least two layers of other layers (J), and more preferably has a substrate (X), an inorganic vapor-deposited layer (Y) and an outer coating (Z) between the aforementioned at least two layers of other layers (J).
[0088] The multilayer structure of the present invention may include an ink layer for printing a product name or pattern, etc. As the ink layer, for example, a coating obtained by drying a liquid containing a polyurethane resin containing a pigment (such as titanium dioxide) dispersed in a solvent, a coating obtained by drying a polyurethane resin containing no pigment, an ink containing other resins as a main agent, or an anti-etching agent for forming electronic circuit wiring. As a coating method for the ink layer, in addition to the gravure printing method, various coating methods such as a wire rod, a spin coater, and a die coater can be listed. The thickness of the ink layer is preferably 0.5 μm or more and 10.0 μm or less, and more preferably 1.0 μm or more and 4.0 μm or less.
[0089] By making the outermost layer of the multilayer structure of the present invention into a polyolefin layer, it is possible to impart heat sealability to the multilayer structure or improve the mechanical properties of the multilayer structure. From the viewpoints of heat sealability, improvement of mechanical properties, etc., the polyolefin is preferably polypropylene or polyethylene. In addition, in order to improve the mechanical properties of the multilayer structure, it is preferred to stack at least one film selected from a film formed by polyester, a film formed by polyamide, and a film formed by a hydroxyl-containing polymer. From the viewpoint of improving mechanical properties, the polyester is preferably polyethylene terephthalate (PET), the polyamide is preferably nylon-6, and the hydroxyl-containing polymer is preferably ethylene-vinyl alcohol copolymer.
[0090] The other layer (J) may be a layer formed by extrusion coating lamination. The extrusion coating lamination method that can be used in the present invention is not particularly limited, and a known method can be used. In a typical extrusion coating lamination method, a molten thermoplastic resin is conveyed to a T-die, and the thermoplastic resin taken out from the flat slit of the T-die is cooled to produce a laminated film.
[0091] As extrusion coating lamination methods other than the above-mentioned single lamination method, sandwich lamination method, tandem lamination method, etc. can be cited. Sandwich lamination method is a method of extruding a molten thermoplastic resin onto a first substrate, supplying a second substrate from another unwinder (winding machine), and laminating to produce a laminate. Tandem lamination method is a method of connecting two single laminating machines to produce a laminate composed of 5 layers at a time.
[0092] (Adhesive layer (H))
[0093] In the multilayer structure of the present invention, the inorganic vapor-deposited layer (Y) can be laminated in a manner of direct contact with the substrate (X), or the inorganic vapor-deposited layer (Y) can be laminated on the substrate (X) by means of an adhesive layer (H) disposed between the substrate (X) and the inorganic vapor-deposited layer (Y). By means of the adhesive layer (H), the adhesion between the substrate (X) and the inorganic vapor-deposited layer (Y) is sometimes improved. In addition, when laminating other layers (J) other than the adhesive layer (H), the adhesion between the layers can sometimes be improved by laminating with the adhesive layer (H). As an adhesive constituting the adhesive layer (H), it is preferably a two-liquid reactive polyurethane adhesive in which a polyisocyanate component and a polyol component are mixed and reacted. In addition, by adding a small amount of additives such as a known silane coupling agent, the adhesion can sometimes be further improved. As suitable examples of silane coupling agents, silane coupling agents having reactive groups such as isocyanate groups, epoxy groups, amino groups, urea groups, and mercapto groups can be listed. By firmly bonding the substrate (X) and the inorganic deposited layer (Y) via the adhesive layer (H), the bending resistance of the multilayer structure of the present invention can be further improved.
[0094] When an adhesive layer (H) is disposed between the substrate (X) and the inorganic vapor-deposited layer (Y), the thickness of the adhesive layer (H) is preferably in the range of 0.03 μm or more and 0.18 μm or less. By setting the thickness of the adhesive layer (H) to this range, it is possible to more effectively suppress the deterioration of the barrier properties and appearance when manufacturing or processing the vacuum packaging bag used in the vacuum insulation body of the present invention, and further, it is possible to improve the impact resistance of the vacuum insulation body of the present invention. The thickness of the adhesive layer (H) is more preferably in the range of 0.04 μm or more and 0.14 μm or less, and further preferably in the range of 0.05 μm or more and 0.10 μm or less.
[0095] The multilayer structure of the present invention preferably has an oxygen permeability of 2.0 ml / (m2) as measured in accordance with JIS K7126 at 40°C, 0% RH (carrier gas side) and 90% RH (oxygen supply side) after three reciprocating movements in a Gelbo Flex test in accordance with ASTM F 392. 2 ·day·atm) or less, more preferably 1.0 ml / (m 2·day·atm) or less, more preferably 0.5ml / (m 2 ·day·atm) or less, particularly preferably 0.40 ml / (m 2 Here, "40°C, 0% RH (carrier gas side), 90% RH (oxygen supply side)" means that the relative humidity on the carrier gas side at 40°C is 0% RH, and the relative humidity on the oxygen supply side is 90%, and "2.0 ml / (m 2 ·day·atm)" means: based on the membrane 1m 2 , oxygen pressure difference of 1 atmosphere, 2.0 ml of oxygen passes through every day.
[0096] (Vacuum packaging bag)
[0097] The multilayer structure of the present invention has excellent gas barrier properties after bending, and is therefore effective in suppressing deterioration of gas barrier properties in the manufacture of vacuum packaging bags and the like. The vacuum packaging bag of the present invention comprises the multilayer structure of the present invention. The vacuum packaging bag is generally a packaging bag used to reduce the pressure inside, and comprises a film material including the multilayer structure as a partition wall separating the inside and the outside. The vacuum packaging bag may comprise a plurality of the multilayer structures.
[0098] From the viewpoint of imparting heat sealability or improving mechanical properties, the surface layer of the vacuum packaging bag of the present invention is preferably made into a polyolefin layer (hereinafter sometimes abbreviated as PO layer). The polyolefin constituting the polyolefin layer is preferably polypropylene or polyethylene. In addition, when further improving the mechanical properties of the vacuum packaging bag is emphasized, at least one film selected from a biaxially stretched polypropylene film, a polyester film, a polyamide film and a PVA-based resin film is preferably laminated as the other layer (J). From the viewpoint of improving mechanical properties, the polyester is preferably polyethylene terephthalate (PET), the polyamide is preferably nylon-6, and the PVA-based resin is preferably an ethylene-vinyl alcohol copolymer resin.
[0099] The vacuum packaging bag of the present invention may have the following structure from the layer on the outside of the vacuum insulation body to the layer on the inside. Here, " / " means lamination via an adhesive layer or direct lamination, and " / / " means lamination via an adhesive layer.
[0100] (1) Outer coating (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer
[0101] (2) Polyester layer / / outer coating (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer
[0102] (3) Polyester layer / / Base material (X) / Inorganic vapor deposition layer (Y) / Top coating (Z) / / PO layer
[0103] (4) Polyamide layer / / outer coating (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer
[0104] (5) Polyamide layer / / Base material (X) / Inorganic vapor deposition layer (Y) / Outer coating (Z) / / PO layer
[0105] (6) PO layer / / outer coating (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer
[0106] (7) Outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating (Z) / / PO layer
[0107] (8) Polyester layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating (Z) / / PO layer
[0108] (9) Polyamide layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating (Z) / / PO layer
[0109] (10) PO layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating (Z) / / PO layer
[0110] (11) Polyester layer / inorganic vapor-deposited layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0111] (12) Polyamide layer / inorganic vapor-deposited layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0112] (13) PO layer / inorganic vapor-deposited layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0113] (14) Polyamide layer / inorganic vapor-deposited layer / / outer coating layer (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating layer (Z) / / PO layer
[0114] (15) PO layer / inorganic vapor-deposited layer / / outer coating layer (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating layer (Z) / / PO layer
[0115] (16) Polyamide layer / / Polyester layer / Inorganic vapor-deposited layer / / Outer coating (Z) / Inorganic vapor-deposited layer (Y) / Substrate (X) / / PO layer
[0116] (17) PO layer / / polyester layer / inorganic vapor deposition layer / / outer coating (Z) / inorganic vapor deposition layer (Y) / substrate (X) / / PO layer
[0117] (18) Polyamide layer / / Polyester layer / Aluminum oxide vapor-deposited layer / / Outer coating (Z) / Inorganic vapor-deposited layer (Y) / Substrate (X) / / PO layer
[0118] (19) PO layer / / polyester layer / alumina vapor-deposited layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0119] (20) Polyamide layer / / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating (Z) / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0120] (21) PO layer / / substrate (X) / inorganic vapor-deposited layer (Y) / outer coating (Z) / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0121] (22) Nylon layer / inorganic vapor-deposited layer / polyester layer / / inorganic vapor-deposited layer / polyester layer / / outer coating (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer
[0122] (23) Polyester layer / / Nylon layer / / Outer coating (Z) / Inorganic vapor deposition layer (Y) / Base material (X) / / PO layer
[0123] (24) Nylon layer / / Polyester layer / / Outer coating (Z) / Inorganic vapor deposition layer (Y) / Base material (X) / / PO layer
[0124] (25) Polyester layer / Polyester layer / Inorganic vapor-deposited layer / / Outer coating (Z) / Inorganic vapor-deposited layer (Y) / Substrate (X) / / PO layer
[0125] (26) Polyester layer / aluminum oxide vapor-deposited layer / / polyester layer / aluminum oxide vapor-deposited layer / / outer coating layer (Z) / inorganic vapor-deposited layer (Y) / substrate (X) / / PO layer.
[0126] (Vacuum Insulation)
[0127] The vacuum insulation body of the present invention comprises the vacuum packaging bag of the present invention and a core material arranged inside the vacuum packaging bag, and the interior of the vacuum packaging bag is decompressed. Usually, in the vacuum insulation body of the present invention, the space portion inside the vacuum packaging bag is in a vacuum state. The vacuum state mentioned here does not necessarily mean an absolute vacuum state, but means that the pressure of the space portion inside the vacuum packaging bag is sufficiently lower than the atmospheric pressure. The pressure of the space portion inside the vacuum packaging bag is determined based on the necessary performance and ease of manufacturing, etc., and is usually less than 2kPa (about 15Torr) from the viewpoint of exerting low thermal conductivity performance, preferably less than 200Pa, more preferably less than 20Pa, and further preferably less than 2Pa. The pressure of the space portion inside the vacuum packaging bag can be above 0.001Pa.
[0128] The core material used in the vacuum insulation body of the present invention is not particularly limited as long as it has low thermal conductivity. For example, pearlite powder, silica powder, precipitated silica powder, diatomaceous earth, calcium silicate, glass wool, asbestos, and resin foam (such as styrene foam, urethane foam) can be exemplified as the core material. In addition, hollow containers made of resin or inorganic materials; honeycomb structures, etc. can be used as the core material. In addition, adsorbents that adsorb water vapor or gas, etc., can also be included in the core material as needed.
[0129] The thermal conductivity of the vacuum insulator of the present invention just after manufacture is preferably 7.0 mW / (m・K) or less, and more preferably 6.5 mW / (m・K) or less. On the other hand, the thermal conductivity just after manufacture may be 1.0 mW / (m・K) or more. If the thermal conductivity is 7.0 mW / (m・K) or less, the low thermal conductivity performance of the vacuum insulator tends to be good. If the thermal conductivity is 1.0 mW / (m・K) or more, a vacuum insulator with good low thermal conductivity performance can be obtained at a relatively low cost. Here, "thermal conductivity" refers to a value measured based on JIS A 1412-1 (1999).
[0130] The vacuum insulation body of the present invention has excellent bending resistance, so the thermal conductivity after 90° bending tends to be a good value. The thermal conductivity after 90° bending is preferably 7.5 mW / (m·K) or less, more preferably 7.0 mW / (m·K) or less, and further preferably 6.5 mW / (m·K) or less.
[0131] The method for producing the vacuum insulation body of the present invention is not particularly limited, and a commonly used method can be adopted. For example, by the following methods 1 to 3, a vacuum insulation body of any shape and size can be produced according to the purpose of use.
[0132] (Method 1) First, prepare two multilayer structures in a rectangular shape in top view, each of which has a heat-sealable layer (e.g., a polyolefin layer) disposed on at least one surface. The two multilayer structures are overlapped in such a way that the respective heat-sealable layers are on the inner side, and any three sides are heat-sealed to produce a packaging bag. Next, fill the interior of the packaging bag with a core material. Next, the interior space of the packaging bag is made into a vacuum state, and the last side is directly heat-sealed in this state to obtain a vacuum insulation body.
[0133] (Method 2) First, a multilayer structure having a rectangular shape when viewed from above is folded so that the heat-sealable layer is on the inside, and two arbitrary sides are heat-sealed to produce a packaging bag. Next, a core material is filled into the interior of the packaging bag. Next, the interior space of the packaging bag is made into a vacuum state, and the last side is directly heat-sealed in this state to obtain a vacuum insulation body.
[0134] (Method 3) First, the core material is sandwiched between two multilayer structures or the multilayer structure is bent to sandwich the core material. Next, the overlapping edges of the multilayer structure are heat-sealed with a vacuum exhaust port remaining to produce a packaging bag with the core material disposed therein. Next, the internal space of the packaging bag is made into a vacuum state, and the vacuum exhaust port is directly heat-sealed in this state to obtain a vacuum insulation body.
[0135] As described above, the vacuum insulation body of the present invention is preferably obtained by heat-sealing the multilayer structures of the present invention to each other. The multilayer structure of the present invention has an inorganic vapor-deposited layer (Y), and therefore exhibits the following tendency: it is not easy to cause a thermal bridge (a phenomenon in which the aluminum foil conducts heat and the insulation performance decreases) observed in a vacuum insulation body obtained from a film having a metal foil such as aluminum foil, and exhibits excellent insulation performance. From the viewpoint of suppressing the thermal bridge, the vacuum insulation body of the present invention can be a vacuum insulation body obtained by heat-sealing a film having the multilayer structure of the present invention and a metal foil. As a film having a metal foil, for example, a film having a layer composition of a polyamide layer / / polyester layer / / metal foil / / PO layer, a polyamide layer / / metal foil / / PO layer, and a polyester layer / / metal foil / / PO layer can be cited.
[0136] The vacuum insulator of the present invention can be used for various applications that require cold or heat preservation. In particular, the vacuum insulator is extremely unlikely to deteriorate over time due to low thermal conductivity even when used under high temperature or high humidity, and has a sufficient durability period as an insulating material. Therefore, it is useful for all thermal insulation applications that require low thermal conductivity, such as water heater tanks, hot water toilet tanks, vending machine tanks, fuel cell tanks, automobile tanks, thermal insulation bags for food, etc., thermal insulation applications for plastic bottles or cans, thermal insulation applications for washing machine drums, coffee, tea, etc., and water heaters. Example
[0137] The present invention will be described in more detail below in the examples, etc., but the present invention is not limited to the following examples. It should be noted that the " / " in the examples means that two layers sandwiching the " / " are directly laminated, and the " / / " means that two layers sandwiching the " / / " are laminated with the aid of an adhesive.
[0138] (Materials used in Examples and Comparative Examples)
[0139] ・VM-XL: "Eval (registered trademark) VM-XL" manufactured by Kuraray Co., Ltd., aluminum-deposited biaxially stretched EVOH film (EVOH ethylene unit content: 32 mol%, EVOH saponification degree: 99.9 mol%, thickness: 12 μm)
[0140] ・VM-PET: "VM-PET1510" manufactured by Toray Industries, aluminum-deposited PET film (thickness 12μm)
[0141] ・PET12: "LumiLa (registered trademark) P60" manufactured by Toray Industries, PET film (thickness: 12μm)
[0142] ・PE50: "Unilux (registered trademark) LS760C" manufactured by Idemitsu Unitech Co., Ltd., LLDPE film (thickness 50μm)
[0143] ・Modified PVA (1): Polyvinyl alcohol having a viscosity average degree of polymerization of 1700, a saponification degree of 98 mol%, and a silanol modification amount (ratio of monomer units containing silanol groups (vinyl silanetriol or units in which some of the hydroxyl groups in vinyl silanetriol are alkoxy groups)) of 0.2 mol%
[0144] ・Modified PVA (2): Polyvinyl alcohol with a viscosity average degree of polymerization of 1700 and a saponification degree of 78 mol% (the proportion of monomer units containing ester groups (vinyl acetate units) is about 22 mol%)
[0145] ・Modified PVA (3): Polyvinyl alcohol having a viscosity average degree of polymerization of 1800, a saponification degree of 98 mol%, and an itaconic acid modification amount (ratio of monomer units (vinyl itaconate units) containing a carboxyl group) of 1.0 mol%
[0146] ・PVA (1): Polyvinyl alcohol with a viscosity average polymerization degree of 1700 and a saponification degree of 100 mol %
[0147] ・"Takeluck (registered trademark) A520" (Mitsui Chemicals, Inc., two-component polyurethane adhesive polyol component)
[0148] ・"Takenet (registered trademark) A50" (manufactured by Mitsui Chemicals, Inc., isocyanate component of a two-component polyurethane adhesive).
[0149] (Evaluation method)
[0150] (1) Thickness of outer coating (Z)
[0151] The multilayer structures obtained in the examples and comparative examples were cut with a microtome to prepare sections for cross-sectional observation (thickness 0.3 μm). The prepared sections were fixed to the sample stand with carbon tape and subjected to platinum ion sputtering for 30 seconds at an accelerating voltage of 30 kV. The cross-section of the multilayer structure was observed with a field-release transmission electron microscope [device: SU8000 manufactured by Hitachi High-Tech Norodomics Co., Ltd.] to calculate the thickness of the outer coating (Z). The measurement conditions were: acceleration voltage: 1 kV, magnification: 20,000 times.
[0152] (2) Oxygen permeability after bending
[0153] The multilayer structures obtained in the examples and comparative examples were cut into 20 cm × 25 cm pieces, and a Gelbo Flex test (bending test) was performed using a Gelbo Flex tester (BE-1005) manufactured by Tester Industries, Ltd. in accordance with ASTM F 392. Specifically, the cut multilayer structure was humidified at 23°C and 50% RH, and the humidified multilayer structure was used to form a cylindrical shape with a diameter of 3.5 inches in the same atmosphere, and both ends were fixed to the Gelbo Flex tester, and the initial interval was 7 inches, the interval at the maximum bending was 1 inch, the first 3.5 inches of the stroke were twisted at an angle of 440 degrees, and the subsequent 2.5 inches were linear horizontal movements, and the reciprocating movement was repeated three times.
[0154] The oxygen permeability of the multilayer structure after bending was measured using MOCON OX-TRAN2 / 20 in accordance with JIS K7126 (unit: ml / (m 2 ・day・atm)). The measurement was performed as follows: the multilayer structure was arranged with the vapor deposition layer side facing the oxygen supply side and the substrate side facing the carrier gas side, under the conditions of 40°C, 90% RH, and 1 atmosphere on the oxygen supply side, and under the conditions of 40°C, 0% RH, and 1 atmosphere on the carrier gas side. Nitrogen containing 2% by volume of hydrogen was used as the carrier gas. In addition, the oxygen permeability after bending was evaluated based on the following evaluation criteria.
[0155] A: More than 0.2 and less than 0.3
[0156] B: more than 0.3 and less than 0.4
[0157] C: more than 0.4 and less than 0.5
[0158] D: more than 0.5 and less than 0.6
[0159] E: more than 0.6 and less than 0.8
[0160] F: more than 0.8
[0161] The unit of the above values is "ml / (m 2 ・day・atm)”.
[0162] (3) Thermal conductivity of vacuum insulation
[0163] The multilayer structure (4-2) obtained in Example 4 and Comparative Examples 1 and 2 and the multilayer structures (C1-2) and (C2-2) were used to prepare vacuum insulation bodies. Specifically, the multilayer structure was cut into 20 cm × 25 cm to obtain two sheets of covering materials. The two sheets of covering materials obtained were overlapped in such a way that the PE layers became the inner surfaces of each other, and the three sides were heat-sealed with a width of 10 mm to prepare a packaging bag as a three-sided sealing bag. The opening of the obtained packaging bag was filled with a core material with low thermal conductivity and a small bag containing calcium oxide as an adsorbent, and a vacuum insulation panel manufacturing device (manufactured by エヌ・ピー・シー Co., Ltd., KT-500RD model) was used to seal the packaging bag at a temperature of 20°C and an internal pressure of 1.0 Pa to prepare a vacuum insulation body. The low thermal conductivity core material used was glass fiber dried in an atmosphere of 160°C for 4 hours. After the obtained vacuum insulation body was stored at 23°C and 50%RH for a certain period of time, the thermal conductivity (mW / (m・k)) of the vacuum insulation body was measured using a thermal conductivity measuring device (manufactured by Eikon Seiki Co., Ltd.) with one side of the vacuum insulation body set to 38°C and the other side set to 12°C. The measurement was performed on the vacuum insulation body before bending and after being bent once vertically (90°).
[0164] (4) Maximum intensity ratio (I(B) / I(C) MAX )
[0165] For the multilayer structures obtained in the examples and comparative examples, the depth direction analysis of the outer coating surface was performed based on TOF-SIMS using the "TOF-SIMS5" manufactured by ION-TOF Corporation under the following conditions. Five measurement sites were randomly selected, and the average of the maximum intensity of each fragment was recorded as I (B), and the average of the intensity of the measurement point between the measurement start point and the maximum intensity measurement point of each measurement site was recorded as I (C), and the intensity ratio of each fragment (I (B) / I (C)) was calculated. From the intensity ratios (I (B) / I (C) of each fragment, the maximum intensity ratio (I (B) / I (C)) was determined. MAX ) and its fragments.
[0166] <Measurement Conditions>
[0167] Primary ion source: Bi3 ++ Bu mode, 0.2pA at 25 keV (10kHz)
[0168] Charge correction: Electron Flooding, No Oxygen Flooding
[0169] Sputtering ion source: Ar 1300+ 、2nA at 5KeV(100μsec)
[0170] Measuring range: 500×500μm (Sputtering)
[0171] 250×250μm (128×128pix) Analysis, 128scans
[0172] Sequence: 2 flames analysis / 3 flames sputtering in 1 scan
[0173] Analysis software: Surface Lab 6 (manufactured by ION-TOF Corporation).
[0174] (Production Example 1)
[0175] 2.5 g of modified PVA (1) was mixed with 47.5 g of distilled water, stirred at 90° C. for 1 hour, and then returned to room temperature to obtain a 5% by mass PVA aqueous solution. Next, 24.0 g of the obtained PVA aqueous solution, 8.24 g of distilled water, and 7.76 g of methanol were mixed and stirred at room temperature for 30 minutes to prepare a coating solution (S-1).
[0176] (Manufacturing Example 2 to Manufacturing Example 4)
[0177] Coating solutions (S-2) to (S-4) were prepared by the same method as in Production Example 1, except that modified PVA (2) (Production Example 2), modified PVA (3) (Production Example 3) or PVA (1) (Production Example 4) was used instead of modified PVA (1).
[0178] (Production Example 5)
[0179] 3.42 parts by mass of tetramethoxysilane (TMOS) was dissolved in 4.1 parts by mass of methanol, followed by dissolving 0.68 parts by mass of γ-glycidoxypropyltrimethoxysilane, and then 0.26 parts by mass of distilled water and 0.64 parts by mass of 0.1N (0.1 equivalent) hydrochloric acid were added to prepare a sol, which was then subjected to hydrolysis and condensation reaction at 10° C. for 1 hour while being stirred. The obtained sol was diluted with 9.25 parts by mass of distilled water and then quickly added to 31.7 parts by mass of a 10% by mass aqueous solution of PVA (1) to prepare a coating solution (S-5).
[0180] (Production Example 6)
[0181] 2.5 g of modified PVA (1) was mixed with 47.5 g of distilled water, stirred at 90° C. for 1 hour, and then returned to room temperature to obtain a 5% by mass PVA aqueous solution. Next, 8.0 g of the obtained PVA aqueous solution, 24.08 g of distilled water, and 7.92 g of methanol were mixed and stirred at room temperature for 30 minutes to prepare a coating solution (S-6).
[0182] (Production Example 7)
[0183] 6.0 g of modified PVA (1) was mixed with 44.0 g of distilled water, stirred at 90° C. for 1 hour, and then returned to room temperature to obtain a PVA aqueous solution with a concentration of 12% by mass. Next, 30.0 g of the obtained PVA aqueous solution, 2.72 g of distilled water, and 7.28 g of methanol were mixed and stirred at room temperature for 30 minutes to prepare a coating solution (S-7).
[0184] (Example 1)
[0185] The coating liquid (S-1) was applied to the aluminum-deposited surface of the VM-XL using a bar coater in such a way that the thickness after drying was 30 nm, and then allowed to stand for 3 seconds. Thereafter, the layer was dried at 100°C for 3 minutes to produce a multilayer structure (1-1) stacked in the order of outer coating layer (Z) / aluminum-deposited layer / biaxially stretched EVOH layer. The maximum strength ratio (I(B) / I(C)) of the outer coating layer (Z) of the obtained three-layer multilayer structure (1-1) was measured according to the method described in the above-mentioned evaluation method (4). MAX ). The results are shown in Table 1.
[0186] Two-component adhesives (Takelac A-520 and Takenet A-50) were applied to one side of "PET12" and "PE50", respectively, and laminated in a manner to present a structure of PET12 / adhesive layer / outer coating layer (Z) / aluminum vapor-deposited layer / biaxially stretched EVOH layer / adhesive layer / PE50 to produce a multilayer structure (1-2). For the obtained seven-layer multilayer structure (1-2), the thickness of the outer coating layer (Z) and the oxygen permeability after bending were measured according to the above methods (1) and (2). The results are shown in Table 1.
[0187] (Examples 2 to 11, Comparative Examples 1 to 8)
[0188] The three-layer multilayer structures (2-1) to (11-1) and seven-layer multilayer structures (2-2) to (11-2) of Examples 2 to 11, and the three-layer multilayer structures (C1-1) to (C8-1) and seven-layer multilayer structures (C1-2) to (C8-2) of Comparative Examples 1 to 8 were prepared and evaluated by the same method as in Example 1, except that the layer composition (evaporated film), the type of coating liquid, the standing time after coating, and the thickness of the outer coating layer (Z) were changed as described in Table 1. The results are shown in Table 1. In addition, one of the results of the depth direction analysis (fragmented SiO2) obtained by the TOF-SIMS measurement of Example 4 is shown in Figure 1In addition, the thermal conductivity of the vacuum insulation body was measured for Example 4 and Comparative Examples 1 and 2 according to the method described in (3) above. The results are shown in Table 2.
[0189]
[0190]
[0191] (Examples 12 to 15)
[0192] The same method as in Example 1 was used to prepare three-layer multilayer structures (12-1) to (15-1) and seven-layer multilayer structures (12-2) to (15-2) of Examples 12 to 15, except that the type of coating liquid, the standing time after coating, and the thickness of the outer coating layer (Z) were changed as shown in Table 3. The thickness of the outer coating layer (Z) and the oxygen permeability after bending of the obtained multilayer structures (12-2) to (15-2) were measured according to the methods (1) and (2) above. The results are shown in Table 3.
[0193]
[0194] As can be seen from Examples 1 to 6, when modified PVA (A) is used, good bending resistance is exhibited, and among them, Example 3 in which the thickness of the outer coating layer is 0.09 μm has significantly excellent bending resistance. In addition, as can be seen from Examples 4 to 6, 12 to 15, when modified PVA having a silanol group, an ester group or a carboxyl group is used, good bending resistance is exhibited. When no outer coating layer (Z) is provided as in Comparative Example 1, poor bending resistance is exhibited, and when non-modified PVA is used as in Comparative Examples 2 to 4, poor bending resistance is exhibited. Furthermore, when a PET film is used as a substrate instead of a PVA-based resin film as in Comparative Examples 5 and 6, a significant decrease in gas barrier properties occurs, and when a coating solution obtained by mixing PVA with a silane compound is used as in Comparative Examples 7 and 8, bending resistance also becomes insufficient.
[0195] From the comparison between Examples 4, 7 and 8, it can be seen that if the solid content concentration of the coating liquid used to form the outer coating layer (Z) is different, the maximum intensity ratio (I(B) / I(C)) of TOF-SIMS will be different. MAX ) are different, and there are differences in bending resistance. From this result, it can be considered that if the solid content concentration is appropriate as in Example 4, specific polar groups (in Example 4, the groups that become the source of SiO2 fragments) are likely to be present at the interface of the inorganic vapor-deposited layer (Y), and as a result, the bending resistance is improved.
[0196] From the comparison of Examples 4, 9 to 11, it can be seen that due to the difference in the standing time after applying the coating liquid, the maximum intensity ratio (I(B) / I(C)MAX ) and bending resistance. As in Example 4, when the coating liquid (S-1) was applied by a bar coater and then dried after waiting for 3 seconds, the result showed good bending resistance.
[0197] Figure 1 The maximum intensity ratio (I(B) / I(C)) is shown in the measurement results of the depth direction analysis obtained using TOF-SIMS of Example 4. MAX ) is a schematic diagram of one of the measurement results of SiO2. Figure 1 In the graph, the X-axis (horizontal axis) is the dose density (Dose density, a parameter in the depth direction, the larger the value, the deeper the measurement point), and the Y-axis (vertical axis) is the intensity (Intensity, the intensity of SiO2 fragments, the larger the value, the more there is). From this figure, it can be considered that: in the interface area between the outer coating (Z) and the inorganic vapor deposition layer (Y), the intensity of SiO2 increases, and it can be said that the result that silanol groups are predominantly present at the interface can be revealed. Although it is not certain, it can be considered that: in Example 4, etc., through the interaction between the silanol groups and aluminum as a component of the inorganic vapor deposition layer (Y), the silanol groups will be predominantly present at the interface, and the outer coating (Z) and the inorganic vapor deposition layer (Y) are firmly bonded, thereby suppressing the occurrence of defects in the inorganic vapor deposition film caused by bending, and as a result, it is possible to suppress the reduction in barrier properties caused by bending.
Claims
1. A multilayer structure comprising a substrate (X), an inorganic vapor-deposited layer (Y) and an outer coating layer (Z) in this order, The substrate (X) is formed of a biaxially stretched polyvinyl alcohol-based resin film, The outer coating layer (Z) comprises a modified polyvinyl alcohol (A) having a vinyl alcohol unit (a) and a monomer unit (b) having a polar group other than the vinyl alcohol unit (a), The thickness of the outer coating layer (Z) is 0.003 μm or more and 1 μm or less, The ratio of the monomer unit (b) having a polar group in all monomer units constituting the modified polyvinyl alcohol (A) is 0.05 mol% or more and 30 mol% or less, The content of the modified polyvinyl alcohol (A) in the outer coating layer (Z) is 70% by mass or more.
2. The multilayer structure according to claim 1, wherein The polar group is at least one selected from the group consisting of a carboxyl group, an ester group, and a silanol group.
3. The multilayer structure according to claim 1 or 2, wherein The maximum intensity ratio (I(B) / I(C)) obtained by the following steps (1) to (3) MAX ) is 1.20 or more, (1) Five randomly selected locations on the surface of the outer coating (Z) were analyzed in depth using TOF-SIMS; (2) for each detected fragment, the average value of the maximum intensity of the fragment at each measurement site (I(B)) and the average value of the intensity at the intermediate measurement point between the measurement start point and the maximum intensity measurement point at each measurement site (I(C)) are calculated, and their ratio is taken as the intensity ratio (I(B) / I(C)); (3) The maximum intensity ratio among the intensity ratios (I(B) / I(C)) of each fragment is taken as the maximum intensity ratio (I(B) / I(C)). MAX ). 4 . The multilayer structure according to claim 1 , further comprising another layer (J) in addition to the substrate (X), the inorganic vapor-deposited layer (Y) and the topcoat layer (Z). 5 . The multilayer structure according to claim 4 , comprising at least two other layers (J), and comprising a substrate (X), an inorganic vapor-deposited layer (Y) and an outer coating layer (Z) between the at least two other layers (J).
6. The multilayer structure according to claim 1 or 2, wherein The biaxially stretched polyvinyl alcohol-based resin film is a biaxially stretched film containing, as a main component, an ethylene-vinyl alcohol copolymer having an ethylene unit content of 10 mol % to 65 mol % and a saponification degree of 90 mol % or more.
7. The multilayer structure according to claim 1 or 2, wherein After three reciprocating movements in the Gelbo Flex test based on ASTM F 392, the oxygen permeability measured based on JIS K7126 at 40°C, 0% RH on the carrier gas side, and 90% RH on the oxygen supply side was 2.0 ml / (m 2 ·day·atm) or less. 8 . A vacuum packaging bag comprising the multilayer structure according to claim 1 .
9. A vacuum thermal insulator comprising the vacuum packaging bag according to claim 8 and a core material arranged inside the vacuum packaging bag, wherein the inside is decompressed.
Citation Information
Patent Citations
Vacuum heat insulation material
JP2008114520A
Gas barrier film, gas barrier laminate and method for producing the same
JP2008056861A
Gas barrier laminated film
JP2019064074A
Multilayer structure and product including the same
JP2019104161A
Vacuum heat insulation material
WO2019004324A1